A Review on Web Content Management system (WCMS) Features and Software - Palanisamy, Ram (Recent Research Reviews Journal, 2023)
Web Content Management System, a type of Content Management System, allows an organization to handle digital information on a website by creating and handling content without prior knowledge of programming or markup languages. The management of online material is beneficial for organizational business applications, producing statistics for decision-making and accomplishing results. The components, functions, software, applications, and benefits and drawbacks of online content management systems have been covered in this study.
Keywords: WCMS; CMS; HTML; MySQL